Concerning Some Marrano Threads in The Aesthetic Theory of Theodor W. Adorno - Górski, Jakub (Religions, 2019)
This article is an attempt to re-read the magnum opus of Adorno's philosophy, namely Aesthetic Theory, using an interpretative key offered by Agata Bielik-Robson's book entitled Jewish Cryptotheologies of Late Modernity: Philosophical Marranos. This interpretative key, called by the Author The Marrano Strategy implemented to Adorno's late philosophy allows us to investigate the common points of Adorno's theory of art criticism and modern Jewish thought. Therefore the main question of this text concerns the characteristics of Jewishness and messianicity (Scholem, Derrida) in Adorno's Aesthetic Theory. The thesis that I am attempting to justify is as follows: the implementation of Marrano strategy to the modern art criticism redefines and reverses the relationship between the particular element and the universal domain. Consequently, this dialectical 'appreciation' of the particular establishes a common conceptual field for critical thinking and traditional, religious motifs.